The Impact of Oil Price on Banking Financial Performance in Algeria: A Panel Regression Analysis - Boucheker , Zineb; Noui , Nabila (Finance and Business Economies Review, 2023)
This paper aimed to measure the impact of oil price on the financial performance of commercial banks in Algeria. The empirical side of the paper was based on balanced panel data obtained from 11 commercial banks active in Algeria during The period (2011-2020), using multiple linear regression analysis by applying the standard (FGLS) estimator using the statistical program STATA16. The article concluded that there is a positive and statistically significant effect of oil price (op) on the financial performance of the studied commercial banks active in Algeria expressed as the ROAA and PBT during the period (2011-2020).